Comparison of Cellular Immune Responses to Inactivated Virus Platform COVID-19 Vaccines between Young Adult and Elderly Populations: Implications for Vaccination Strategies - Taureni Hayati (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The COVID-19 pandemic, driven by the SARS-CoV-2 virus, has significantly impacted global health, with the elderly population being particularly vulnerable to high morbidity and mortality. Vaccination has emerged as a critical strategy in controlling virus spread and reducing disease burden, especially among high-risk populations. However, vaccine efficacy in the elderly is a concern due to immunosenescence, which involves the deterioration of immune function with age. Objective: This study aimed to compare the cellular immune response to the inactivated virus platform COVID-19 vaccine between elderly (aged ≥60 years) and young adults (aged 30-40 years), focusing on changes in T cell populations post-vaccination COVID-19. Methods: A prospective cohort study design was used to compare immune responses between 40 elderly and 39 young adults who had received the booster-2 series of the inactivated virus COVID-19 vaccine and were eligible for a booster dose. Blood samples were collected before vaccination and four weeks after the booster-2 to analyze CD4+ and CD8+ T cell subsets using flow cytometry. Results: The study revealed significant differences in the immune responses between the two age groups. Elderly individuals showed a lesser increase in naïve and memory T cells compared to younger adults, indicating a diminished response to the booster vaccination. Conclusion: The findings suggest that vaccination strategies may need to be tailored to enhance immune responses in the elderly, potentially involving adjusted doses or vaccine formulations. This study provides a scientific basis for optimizing COVID-19 vaccination protocols for the elderly and highlights the challenges of immunosenescence.